Experimental analysis of nanofluids in PEMFC cooling plate integrated with thermoelectric generator / A. A. Zailan, I. A. Zakaria and A. N. Zarizi - Zailan, A. A.; Zakaria, Irnie Azlin; Zarizi, A. N. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
A thermoelectric generator (TEG) is considered a feasible option to recover waste heat from a Proton exchange membrane fuel cell (PEMFC) into electrical energy. However, its application is limited due to its low efficiency. Meanwhile, nanofluids have emerged as an alternative coolant in heat transfer due to their superior thermal conductivity characteristics. Thus, this study aims to improve the efficiency of the TEG using nanofluids.